1991
DOI: 10.1128/iai.59.7.2396-2402.1991
|View full text |Cite
|
Sign up to set email alerts
|

Production of granulocyte-macrophage colony-stimulating factor (GM-CSF) by monocytes and large granular lymphocytes stimulated with Mycobacterium avium-M. intracellulare: activation of bactericidal activity by GM-CSF

Abstract: Treatment of monocytes with recombinant granulocyte-macrophage colony-stimulating factor (GM-CSF) was shown to enhance their antimycobacterial activity in an in vitro assay. Furthermore, Mycobacterium avium-M. intracellulare was found to induce the production of this hemopoietic growth factor. Human peripheral blood mononuclear cells were fractionated by plastic adherence and Percoll density centrifugation, and each population of cells was stimulated with mycobacteria. GM-CSF was produced by both monocytes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(9 citation statements)
references
References 31 publications
1
7
0
1
Order By: Relevance
“…In the present study we have confirmed previous investigations that human peripheral blood monocytes release the haematopoietic pro‐inflammatory cytokine, GM‐CSF in response to bacterial LPS (Blanchard et al ., 1991; de Waal Malefyt et al ., 1991; Meja et al ., 2000). In addition, we have extended this finding by providing evidence that cyclic AMP‐elevating drugs act at both the transcriptional and post‐transcriptional level to suppress GM‐CSF output by a mechanism that is not mediated by IL‐10.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study we have confirmed previous investigations that human peripheral blood monocytes release the haematopoietic pro‐inflammatory cytokine, GM‐CSF in response to bacterial LPS (Blanchard et al ., 1991; de Waal Malefyt et al ., 1991; Meja et al ., 2000). In addition, we have extended this finding by providing evidence that cyclic AMP‐elevating drugs act at both the transcriptional and post‐transcriptional level to suppress GM‐CSF output by a mechanism that is not mediated by IL‐10.…”
Section: Discussionsupporting
confidence: 92%
“…Granulocyte/macrophage colony‐stimulating factor (GM‐CSF) is a 14 – 35 kDa acidic glycoprotein that is secreted by many cells including those of the human monocyte/macrophage lineage (Blanchard et al ., 1991; Meja et al ., 2000; Sallerfors & Olofsson, 1992). Many studies, in vitro and in vivo , have shown that GM‐CSF primes and activates a wide variety of inflammatory and immune cells and is implicated in the pathogenesis of a number of respiratory diseases including chronic obstructive pulmonary disease (COPD) and asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Although a comprehensive understanding of M. avium 's pathogenesis has not yet evolved, it can be concluded that the initial interaction of the immune system with M. avium is multifactorial (1,76,77). Cytokine responses that have been evaluated include IL-1 alpha, IL-1 beta, IL-6, IL-10, TNF-alpha, and TGF-beta (57,78,79,80,81,82,83). Other studies report an immunosuppressive capacity of M. avium associated with prostaglandin E 2 (PGE 2 ) (84,85,86,87,88).…”
Section: Cytokines Important In Host Responsementioning
confidence: 99%
“…Granulocyte/macrophage colony‐stimulating factor (GM‐CSF) is a variably glycosylated cytokine produced by many cells including those of the human monocyte/macrophage lineage ( Blanchard et al ., 1991 ; Sallerfors & Olofsson, 1992 ). GM‐CSF is implicated in a number of respiratory diseases including asthma ( Broide et al ., 1991 ; 1992a , 1992b ; Brown et al ., 1991 ; Davies et al ., 1995 ; Hallsworth et al ., 1994 ; Lai et al ., 1996 ; Lei et al ., 1998 ; Nakamura et al ., 1993 ; Sousa et al ., 1993 ; Till et al ., 1995 ; Woolley et al ., 1995 ; Xing et al ., 1996 ) where it is a potent pro‐inflammatory stimulus.…”
Section: Introductionmentioning
confidence: 99%